Research Explorer – Technical Documentation of Routines - Wilfried Ehrenfeld (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
The Research Explorer is a directory of institutes at German universities and non-university research facilities, which is provided by the German Research Foundation (DFG) and the German Academic Exchange Service (DAAD). It is available for download for free and currently comprises ca. 23,000 entries. Two versions of this directory, which differ with regard to depth and coverage, are available to us. One version comprises 1712 entries, while the other holds over 22,000. Primary goal of the presented routines is the comparison and complement of these two versions of the Research Explorer. The necessity for this arises from the differences in depth and coverage of the different versions. Furthermore, both versions are incomplete at some points, which means that individual institutions had to be added manually. The resulting data sets of the modified Research Explorer can subsequently be used for the mapping of cooperation relations. – – Der Research Explorer ist ein von der Deutschen Forschungsgemeinschaft (DFG) und der Deutschen Akademischen Austauschdienstes (DAAD) zur Verfügung gestelltes Verzeichnis von Instituten an deutschen Hochschulen sowie außeruniversitäre Forschungseinrichtungen. Er steht kostenlos zum Download bereit und umfasst ca. 23.000 Einträge. Uns liegen zwei verschiedene Abzüge dieses Verzeichnisses vor, die sich jedoch in Abdeckung und Tiefe unterscheiden. Die eine Version umfasst 1712 Einträge, die andere über 22.000.
Keywords: 330